IDENTIFICATION, CHARACTERIZATION AND EVALUATION OF HIGH AMYLOPECTIN SORGHUM (Sorghum bicolor (L.) Moench) GERMPLASM LINES - C.V. RATNAVATHI, P. SANJANA REDDY and (The Journal of Research, PJTSAU, 2019)
Exploring alternate uses for sorghum has become imperative owing to the decreasing area under sorghum. Among the diverse alternatives available, high amylopectin sorghum can serve for industrial uses for ethanol, adhesives, lubricants among others. Thirteen high amylopectin lines were identified from among the 4000 germplasm lines tested using rapid iodine technique. These 13 high amylopectin lines were evaluated in four environments for agronomic, yield and quality traits along with checks. Wide variability was found among the germplasm lines. The lines interacted significantly with the environment and the interaction effects were also significant though the numerical differences were marginal. Based on grain color, grain yield and amylopectin content, the germplasm lines IS 2269 in red grain color background and IS 5624 in white grain color background were found promising for grain yield as well as early flowering.